The Concept of Munkar in al-Dhahabī’s Critique of al-Ḥākim’s Hadith Authentication in al-Mustadrak - Abbas, Sanaa Fadel; Rawabdeh, Maessa Ali (Jurnal Studi Ilmu-ilmu Al-Qur'an dan Hadis, 2025)
The exclusion of certain hadiths by the compilers of al-Shaykhān (Ṣaḥīḥ al-Bukhārī and Ṣaḥīḥ Muslim), despite their acceptance of the same transmitters in other narrations, indicates the presence of particular flaws within those reports. This selective process has generated substantial discussion in the field of hadith criticism, especially around the notion of “authentication according to their conditions.” Scholarly debates have long centered on how such conditions were defined, interpreted, and applied by later critics. This study explores the methodological divergence between al-Ḥākim al-Nīsābūrī (d. 405/1014) and al-Dhahabī (d. 748/1348) concerning the use of Bukhārī and Muslim’s criteria as benchmarks for authenticity. Specifically, it examines hadiths that al-Ḥākim classified as “authentic according to the conditions of al-Shaykhān or one of them,” but which al-Dhahabī subsequently rejected as munkar. Through an inductive-critical approach, the analysis engages six representative cases drawn from al-Mustadrak and Talkhīṣ al-Mustadrak, allowing for a close reading of how both scholars articulated and operationalized their respective standards. The findings suggest that al-Ḥākim’s approach to authentication was often generous, at times overlooking structural and contextual defects, whereas al-Dhahabī’s assessments reflected a stricter evaluative framework. His judgments of munkar frequently rested on the identification of weak transmitters, disrupted isnād structures, or questionable transmission contexts. Beyond highlighting their methodological contrast, this study raises broader questions about the coherence and applicability of “conditions of the Shaykhān” as a category of hadith validation. Rather than closing the debate, the cases underscore the interpretive tensions within classical hadith criticism and invite further inquiry into how later scholars negotiated between textual authority and critical scrutiny.